THE EFFECT OF THIN CAPITALIZATION, CAPITAL INTENSITY, AND DEFERRED TAX EXPENSE ON TAX AVOIDANCE - Do’a Fani Febilia; Siti Isnaniati; Dewi Wungkus (RADJA PUBLIKA, 2025)
The purpose of this study is to analyze the effect of thin capitalization, capital intensity, and defined tax liabilities on tax avoidance. The research method uses a quantitative approach with multiple linear regression analysis. The research population consists of manufacturing companies in the goods and consumer goods industry for the period 2021-2023, wih a sample size of 20 companies and 60 data observations. According to the analysis results, thin capitalization does not affect tax avoidance, but capital intensity affects tax avoidance and defined tax liabilities affect tax avoidance. This study shows that there is a negative effect between thin capitalization and tax avoidance. The novelty of this study lies in the research object and the data period used.